Antiresorptive agents enhance ossification of free flap reconstructions of the mandible: a radiological retrospective cohort study - Maximilian Gottsauner; Johannes Meier; Jonas Eichberger; Stephanie Eckmüller; Johannes Schuderer; Mathias Fiedler; Michael Maurer; Torsten E. Reichert; Tobias Ettl (Frontiers in Oncology, 2024)
BackgroundThe aim of this study was to investigate the effect of antiresorptive agents on the ossification of reconstructed mandibles by free bone grafts for the first time.MethodsA total of 38 reconstructions of the jaw were retrospectively evaluated for ossification between bone segments by two raters based on postoperative panoramic radiographs. The study group (n = 13) had segmental resection of the mandible and free bone flap reconstruction due to medication-related osteonecrosis of the jaw (MRONJ). The control group (noMRONJ, n = 25) comprised segmental mandibular resections and free bone flap reconstructions due to tumors, chronic osteomyelitis, or trauma without any radiation. Ossification time and influencing factors were evaluated.ResultsBoth duration of surgery (346 ± 90 min. vs. 498 ± 124 min.; p < 0.001) and hospitalization (8.7 ± 2.8 days vs. 13.4 ± 5.3 days, p = 0.006) were shorter in the MRONJ group compared to the noMRONJ group. Ossification after mandibular reconstruction was significantly faster in the MRONJ study group [224 days, interquartile range (IQR) 175–287] compared to the control group (288 days, IQR 194–445; p < 0.001). Moreover, good initial contact between the segments resulted in faster ossification (p < 0.001) in the MRONJ group. Ossification rate between original and grafted bone or between grafted bone segments only did not differ in both the study and control groups (MRONJ, p = 0.705 vs. control, p = 0.292). The type of antiresorptive agent did not show any significance for ossification. The rate of wound healing disturbances did also not differ between the study and control groups (p = 0.69).ConclusionAdvanced MRONJ (stage 3) can be resected and reconstructed safely with free microvascular bone flaps. Antiresorptive agents enhance the ossification of the bone segments. Optimal initial contact of the bone segments accelerates bone healing. Surgery and hospitalization are markedly shortened in this vulnerable group of MRONJ patients compared to oncologic patients.